Case Report: Retroperitoneal bronchogenic cyst mimicking adrenal mass: Clinical implications and comprehensive literature analysis - Xiang, Shengxiang; Hao, Jiange; Zong, Xiaowen; Wen, Shuang; Zhang, Jingxuan; Chen, Chunyu; Hao, Jiayi; Song, Zhuwei; Tong, Heyao; Wang, Liang; Fan, Bo; Liu, Zhiyu (Frontiers in Oncology, 2025)
BackgroundBronchogenic cysts are benign congenital anomalies originating from embryonic foregut development. Although typically located in the mediastinum or lung parenchyma, retroperitoneal bronchogenic cysts are exceedingly rare, with only a limited number of cases reported in the literature. We present a case of a bronchogenic cyst situated in the left retroperitoneal space, along with a concise review of previously documented cases, summarizing their common epidemiological, clinicopathological, and prognostic features.Case summaryA 48-year-old female was admitted with unexplained left lumbar pain. Computed tomography (CT) revealed a slightly hyperdense cystic mass measuring 43×37×36 mm in the left adrenal region. The lesion was successfully resected using robot-assisted laparoscopic surgery. Histopathological examination confirmed the diagnosis of a bronchogenic cyst. The patient remained hemodynamically stable and recovered well postoperatively. At the 6-month follow-up, she remained asymptomatic with no evidence of recurrence.ConclusionGiven the rarity of retroperitoneal bronchogenic cysts, preoperative imaging is often insufficient to definitively differentiate them from other retroperitoneal neoplasms. Consequently, definitive diagnosis usually depends on postoperative pathological evaluation. This case highlights the diagnostic challenge posed by this rare entity and underscores the importance of pathological examination for definitive diagnosis.